2018
DOI: 10.3390/computation6030043
|View full text |Cite
|
Sign up to set email alerts
|

Application of Different Turbulence Models Simulating Wind Flow in Complex Terrain: A Case Study for the WindForS Test Site

Abstract: A model for the simulation of wind flow in complex terrain is presented based on the Reynolds averaged Navier-Stokes (RANS) equations. For the description of turbulence, the standard k-ε, the renormalization group (RNG) k-ε, and a Reynolds stress turbulence model are applied. Additional terms are implemented in the momentum equations to describe stratification of the Earth's atmosphere and to account for the Coriolis forces driven by the Earth's rotation, as well as for the drag force due to forested canopy. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…The long blades of modern wind turbines reach down into this area with stronger turbulence in the lee of the trees. Knaus et al (2018) showed that not only orographic effects, but also lee effects of trees affect the flow over an escarpment at these heights. The model results show a significant increase of the turbulence kinetic energy (TKE, k) and a minimum in wind speed below 50 m above ground in the lee of the trees (Knaus et al 2018).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The long blades of modern wind turbines reach down into this area with stronger turbulence in the lee of the trees. Knaus et al (2018) showed that not only orographic effects, but also lee effects of trees affect the flow over an escarpment at these heights. The model results show a significant increase of the turbulence kinetic energy (TKE, k) and a minimum in wind speed below 50 m above ground in the lee of the trees (Knaus et al 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Measurements and simulations showed an accelerated flow over the escarpment with westerly winds. Due to surface roughness and the orography, the strongest turbulence fluctuations and flow acceleration were observed at the lowest 10 to 80 m above ground upstream of the escarpment (Knaus et al 2018;Letzgus et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common coupling methods is the one-way approach where the mesoscale model is coupled to the microscale model through the lateral boundaries at fixed times (time-slice). This approach has been successfully applied in complex terrain by several authors as [18][19][20] among others.…”
Section: Introductionmentioning
confidence: 99%
“…ANSYS CFD has a few number of methods or turbulent models for the simulation of geometric models such as SST model, k-ε model, LES model and k-ω model. And for the present study which is an atmospheric boundary-layer study, a realizable k-ε model has been used because of its suitability [40][41][42]. The past studies show the efficiency of the method.…”
Section: Introductionmentioning
confidence: 99%